The effect of myotoxins isolated from Bothrops snake venoms on multilamellar liposomes: relationship to phospholipase A2, anticoagulant and myotoxic activities - Díaz Oreiro, Cecilia (1991)
The effect of four myotoxins isolated from Bothrops snake venoms on the release of peroxidase trapped in large multilamellar liposomes was studied and correlated to their phospholipase A2, myotoxic and anticoagulant activities. The four myotoxins affected negatively-charged liposomes in a dose-dependent way, having no effect on positively-charged liposomes. Conditions that inhibited phospholipase A2 activity, i.e., substitution of calcium by EDTA, reduced liposome-disrupting activity of Bothrops asper myotoxin I and Bothrops atrox myotoxin, both of which have high phospholipase A2 activity, but did not affect the action of B. asper myotoxin II and Bothrops moojeni myotoxin II, which have extremely low phospholipase A2 activity. However, all myotoxins disrupted to some extent negatively-charged liposomes under conditions where phospholipase A2 activity was abolished. Since these toxins behave as amphiphilic proteins in charge-shift electrophoresis, it is suggested that membrane-disorganization is at least partially due to a non-enzymatic penetration and alteration of bilayers. There was no strict correlation between liposome-disrupting activity and myotoxicity in vivo. Thus, although both effects probably depend on the toxins' ability to disturb membranes, it is likely that variation in complexity between skeletal muscle plasma membrane and liposome bilayers are the basis for this difference. The anticoagulant effect seems to depend on the ability of the toxins to enzymatically degrade phospholipids, since only B. asper myotoxin I and B. atrox myotoxin prolonged the plasma recalcification time.